Comparison of Carboxyhemoglobin (COHb) Levels in the Blood of Active and Passive Smokers in Bulupitu Bus Terminal Workers, Banyumas Regency - Noviani Nur Hayati; Kurnia Ritma Dhanti; Retno Sulistiyowati; Tantri Analisawati Sudarsono (Jurnal Analis Medika Biosains (JAMBS), 2023)
Carbon monoxide (CO) is a colorless, tasteless, and odorless gas, but in high concentrations in the blood, it can cause death. One of the CO2 can come from cigarette smoke. When cigarette smoke is inhaled, the affinity of CO with the blood is stronger than for oxygen, and this will increase the carboxyhemoglobin (HbCO) in the blood. Passive smokers who are often near active smokers will inhale cigarette smoke. This study aims to compare HbCO levels in the blood between active and passive smokers of Bulupitu terminal workers, Banyumas Regency. This was an analytical observational study with six active and six passive smokers who are terminal workers. All active and passive smokers samples had HbCO concentrations above the normal HbCO threshold of 3.5%. The measurement results showed the average HbCO level of smokers was 5.87%. Determining differences in HbCO levels in the blood of active and passive smokers was conducted using the Independent Test (p-value = 0.370). This value shows no significant difference in blood HbCO levels in active and passive smokers.